The Development of Psychology, Psychological Research and Professional Practice in Barbados - Maynard, Donna-Maria Bradshaw (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Abstract The article outlines the history and the development of psychological research and practice in terms of its strengths and weaknesses. Strengths identified include local university support of psychology as a discipline, high demand from students for the psychology programmes, good teaching in the undergraduate programmes, and government regulation of the profession. Weaknesses include that there are no laboratory facilities available at the major training institution, internship sites are scarce and few opportunities exist to be supervised by a Ph.D. or Psy.D. Psychologist. With the support of findings from a small scale qualitative study addressing the opportunities available to psychology graduates interested in pursuing a career in clinical psychology. In conclusion the future of psychology in Barbados looks promising, with the prospect of engaging Information Communications Technologies to aid supervision and reaching clients who would not otherwise have access to psychological services. Abstracto El artículo describe la historia y el desarrollo de la investigación psicológica y la práctica en términos de sus fortalezas y debilidades. Fortalezas identificadas incluyen soporte universidad local de la psicología como disciplina, la alta demanda de los estudiantes para las carreras de psicología, enseñanza bien en los programas de pregrado, y la regulación gubernamental de la profesión. Las debilidades son que no existen instalaciones de laboratorio disponibles en la institución principal de formación, los sitios de prácticas son escasos y existen pocas oportunidades para ser supervisado por un doctor o Psy.D. Psicólogo. Con el apoyo de las conclusiones de un estudio cualitativo pequeña escala frente a las oportunidades disponibles para los graduados de psicología interesados ​​en seguir una carrera en psicología clínica. En conclusión, el futuro de la psicología en Barbados parece prometedor, con la posibilidad de contratar Comunicaciones Tecnologías de la Información para facilitar la supervisión y llegar a los clientes que de otra forma no tendrían acceso a los servicios psicológicos.